Secret fleets : Fremantle's World War II submarine base - Cairns, Lynne (Western Australian Museum, 2013)
Contrary to what many Australians believe, during 1942 Japanese submarines were active in Australian waters and Japanese spy planes made surveillance flights over our major cities. With enemy submarines patrolling off the Western Australian coast, Fremantle became an important international submarine base, the largest in the Southern Hemisphere. During the war Fremantle played host to over 170 Allied submarines, with submarines of the United States, British and Dutch navies making a total of 416 war patrols out of the port between March 1942 and August 1945. The secrecy surrounding the operati.